Transmisi Keilmuan Pesantren di Ruang Alumni: Studi Sosiologis atas Praktik Ngaji dan Silaturahmi dalam Majlis al-Hikam - Shalih, Badrus; Marzuqi, Marzuqi; Sahraman, sahrahman (Lembaga Yasin AlSys, 2026)
Studies on the post-graduation transmission of pesantren knowledge remain limited in the literature on the sociology of Islamic education in Indonesia because previous research has focused more on the internal dynamics of institutions than on the role of alumni as agents of scholarly reproduction. This study aimed to analyze the mechanisms of pesantren knowledge transmission and the reproduction of pesantren habitus within the alumni social space through the Majlis Al-Hikam forum. This study employed a qualitative approach with an ethnographic design and an intensive single-case study conducted over eight months, from September 2025 to April 2026. Data were collected through participant observation, in-depth interviews with 22 informants, and document analysis, then analyzed inductively using modified grounded theory. The results showed that the practice of ngaji functions as a mechanism of scholarly transmission with relational-spiritual dimensions, rather than merely as the transfer of texts, marked by the reproduction of adab and the charismatic authority of the Teacher outside the institutional space of the pesantren. The practice of silaturahmi also functions as an investment in bonding and bridging social capital, enabling the conversion of social capital into economic and symbolic capital. These findings extend Bourdieu’s concept of habitus by showing that pesantren habitus is not only formed within institutions but is also actively reproduced and negotiated in alternative social spaces created by alumni. Thus, this study affirms that the post-graduation transmission of pesantren knowledge is a dynamic process that goes beyond the nostalgic preservation of scholarly tradition, while also making a theoretical contribution to the development of the sociology of Islamic education and pesantren alumni studies.